Cognitive Impairment following Adult Spinal Deformity Surgery. Issue 1 (April 2016) - Nabiyev, Vugar; Ayhan, Selim; Yuksel, Selcem; Mmopelwa, Tiro; Sabat, Montse Domingo; Pellise, Ferran; Alanay, Ahmet; Perez-Grueso, Francisco Javier Sanchez; Kleinstuck, Frank; Obeid, Ibrahim; Acaroglu, Emre; ,
Introduction: Elderly patients undergoing major surgery may experience cognitive deterioration due to lesser plasticity in their brain tissue. This so called postoperative cognitive dysfunction (POCD) syndrome is characterized with non-specific dysfunction in memory, concentration and analysis skills. It is not known whether adult spinal deformity (ASD) surgery is associated with POCD. Purpose of this study is to analyze the cognitive abilities of older patients undergoing spinal deformity surgery before and after the surgery so as to understand whether ASD surgery is associated with POCD. Material and Methods: A prospective longitudinal study was performed on surgical patients older than 50 years enrolled in a prospective multi-centric database. Mini mental state examination (MMSE) was performed to assess cognitive functions in addition to the health related quality of life (HRQOL) tests (SF-36, ODI and SRS-22) at preoperative, post-operative 6th week and 6th month points. Demographics, preoperative health status, comorbidities, surgical characteristics were also analyzed. Descriptive statistics and repeated measures of variance analysis were performed. Results: A total of 90 patients with a mean age of 67.4 ± 8.2 were enrolled in the study; all had 6th week and 58 had both 6th week and 6th month follow-up MMSE evaluations. Averages (standard deviation) of surgical time, estimated blood loss (EBL), number of screws used and hospital stay were 240.1 (111.9)min, 1621.2 (1058.7)ml, 11.2 (4.4) and 14.2 (11.45)days respectively. On analysis, it was seen that there was even a slight increase in mean MMSE score (p > 0.05) between time points (Table 1). There was a decrease of > 2 points (3 or 4 points) in 6 patients (6.7%) at both time points. Conclusion: Although ASD surgery in older patients is recognized as challenging, this study suggests that it is not necessarily associated with a significant deterioration in the cognitive abilities of patients undergoing it. These results are different compared with those reported for other major surgical interventions. This may be due to the relatively minor influence of ASD itself on the cognitive abilities of the patients involved as well as to the relatively stable hemodynamic conditions obtainable during modern ASD surgery.